Clinical gynecologic endocrinology and infertility - Fritz, Marc A. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
Established for more than thirty years as one of the world's most widely read gynecology texts, Clinical Gynecologic Endocrinology and Infertility is now in its Eighth Edition. In a clear, user-friendly style enhanced by abundant illustrations, algorithms, and tables, the book provides a complete explanation of the female endocrine system and its disorders and offers practical guidance on evaluation and treatment of female endocrine problems and infertility. Major sections cover reproductive physiology, clinical endocrinology, contraception and infertility. This edition has a modern full-color design.